Black Phosphorus—Diketopyrrolopyrrole Polymer Semiconductor Hybrid for Enhanced Charge Transfer and Photodetection. Issue 11 (24th August 2021) - Low, Mei Xian; Kuriakose, Sruthi; Liu, Qian; Taylor, Patrick D.; Dong, Dashen; Yang, Terry Chien-Jen; Ahmed, Taimur; Wilson, Gregory; Spencer, Michelle J. S.; Tawfik, Sherif Abdulkader; Sriram, Sharath; Bhaskaran, Madhu; et al.
Abstract : Black phosphorus (BP) has emerged as an exciting 2D material for optics, photonics, and electronics. However, there are few studies on BP in terms of modulation and enhancement of their electronic and optical properties and their concurrent reactivity and hence reduction after exposure to the ambient environment. To resolve such challenges, creating inorganic–organic hybrid materials is a suitable approach that offers significant opportunities to enhance the utility of BP by combining them with an organic material which has a complementary set of properties. Herein, a hybrid‐layered BP material coupled with a low bandgap donor–acceptor organic semiconducting polymer, selenophene‐flanked diketopyrrolopyrrole with thienyl‐vinylene‐thienyl (PDPPSe–TVT) is reported, to broaden the optical absorption and tune the ambipolar field effect transistor characteristics. A highly sensitive, nongated broadband photodetection capability of the hybrid device with a detection range from UV–vis to near‐IR (280–1050 nm) and responsivities of up to 4.22 × 10 3 A W −1 in ambient conditions. In addition to improved photodetection, simultaneous enhancement in both hole (71%) and electron (91%) mobilities is achieved while protecting the sensitive BP material from rapid environmental degradation. The findings therefore report a breakthrough in enhancing the utility of BP as a light‐active material for versatile photonics and electronics applications without operating in an inert environment. Abstract : Hybridization of black phosphorus (BP) with an organic semiconducting polymer (PDPPSe–TVT) enables the formation of a nongated, highly sensitive and broadband 2D photodetector. This approach also protects BP from ambient degradation, which facilitates the use of BP in photonics applications while operating in ambient environments.